Development of the Bacapeta Learning Media Platform to Support Students’ Geospatial Technology Learning - Eka Novia Marianti; Purwanto Purwanto (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
The spatial literacy skills and mastery of geospatial technology among senior high school students in Indonesia remain relatively low, as indicated by limited use of Geographic Information Systems (GIS) technology in learning and low academic achievement in mapping materials. This condition requires innovation in learning media to facilitate concrete learning experiences aligned with the demands of 21st-century Geography learning. This study used the Research and Development (R&D) method with the ADDIE model, comprising the analysis, design, development, implementation, and evaluation stages. This study used a mixed-methods approach, using instrument questionnaires to assess the feasibility and validity of the learning media. This study aimed to determine the feasibility level and validity level of the developed learning media. The results of the study showed that the average feasibility score for the learning media from media experts was 88%, with a very valid qualification, while the score from material experts was 90.4%, with a very valid qualification. The trial results of the Bacapeta web-based learning media also obtained scores of 97.5% from teachers, indicating a very feasible response, and 93.4% from students, with a very feasible qualification. These results indicate that the Bacapeta web is feasible for use in the learning process to support the spatial literacy abilities of senior high school students